Intraindividual variation of the transversus abdominis plane block: an exploratory study in healthy volunteers. Issue 6 (15th April 2020) - Juhl, Christian Svendsen; Rothe, Christian; Støving, Kion; Aasvang, Eske K; Rosenstock, Charlotte V; Lange, Kai Henrik Wiborg; Lundstrøm, Lars Hyldborg
Abstract : Introduction: The transversus abdominis plane block is widely used in postoperative pain management after abdominal surgery. However, large interindividual variation in the cutaneous distribution area of the block has been demonstrated. The purpose of the present study was to explore the reproducibility of the block by determining the intraindividual variation when repeating the block on two separate days. Methods: Ultrasound-guided posterior transversus abdominis plane blocks were performed in 16 healthy volunteers and repeated after at least 2 days. Cutaneous sensory block areas and distributions, thresholds for mechanical stimulation, abdominal muscle thicknesses at rest and during maximal contraction, waist circumferences and block duration times were measured on both days. Outcome measurements from the 2 days were compared using a one-sample t-test and intraclass correlation coefficients were calculated for each parameter. Agreement was evaluated visually using Bland-Altman plots. Results: None of the mean values of the outcome measurements differed significantly between the 2 days. Intraclass correlation coefficient was 0.75 (moderate-to-good reliability) for lateral abdominal muscle thickness during maximal contraction, but ranges from −0.07 to 0.67 were found for all other outcome measurements (poor-to-moderate reliability). Conclusion: We found a moderate-to-good reproducibility for lateral abdominal muscle thickness during maximal voluntary contraction, but a moderate-to-poor reproducibility for all other block characteristics. However, the cutaneous distribution of the block was still located primarily inferior to a horizontal line through the umbilicus and lateral relative to a vertical line through the anterior superior iliac spine.